Differences in the movement skills and physical qualities of elite senior and academy rugby league players - Ireton, M. R. E.; Till, K.; Weaving, D.; Jones, B. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to investigate (a) the differences in the movement skills and physical qualities between academy and senior rugby league players and (b) the relationships between movement skills and physical qualities. Fifty-five male rugby league players (Senior, n = 18; Under 19 n = 23; Under 16, n = 14) undertook a physical testing battery, including anthropometric (stature and body mass), strength (isometric midthigh pull; IMTP), and power (countermovement jump; CMJ) qualities, alongside the athletic ability assessment (AAA; comprised of overhead squat, double lunge, single-leg Romanian deadlift, press-up, and pull-up exercises). Univariate analysis of variance demonstrated significant (p < 0.001) differences in body mass, IMTP peak force, CMJ mean power, and AAA movement skills between groups. The greatest observed differences for total movement skills, peak force, and mean power were identified between Under 16 and 19 academy age groups. Spearman's rank correlation coefficients demonstrated a significant moderate (r = 0.31) relationship between peak force and total movement skills. Furthermore, trivial (r = 0.01) and small (r = 0.13; r = 0.22) relationships were observed between power qualities and total movement skills. These findings highlight that both movement skills and physical qualities differentiate between academy age groups, and provides comparative data for English senior and academy rugby league players.